STRATEGI COPING STRESS AKADEMIK MENGGUNAKAN PENDEKATAN SPIRITUAL UNTUK MENINGKATKAN RESILIENSI MAHASISWA - Sari, Dewi Purnama; Sutarto, Sutarto (Psikis : Jurnal Psikologi Islami, 2023)
Academic stress can have a significant impact on students, both their thoughts, behaviour and emotions. Therefore, their resilience needs to be increased to resolve their problems immediately. This phenomenological research aims to explore students' experiences in increasing resilience due to academic stress by using a spiritual approach. Research informants comprised 10 students who succeeded in increasing resilience due to academic stress with coping strategies using a spiritual approach. The research data were obtained through interviews, analyzed using the Melis and Huberman analysis model, and then checked the validity of the data by submerging triangulation and extending the observations. The study results show that students use three coping strategies with a spiritual approach to deal with academic stress. First is positive thinking, which is always optimistic about the problems faced. Believing that in every problem faced, there is always a silver lining and there is a way out. Second, positive action always tries to solve problems by carrying out various positive activities. Third, positive hopping, namely always hoping and praying to Allah SWT so that he will be given strength, convenience and guidance in overcoming problems